Political relations between South Korea and Japan: Towards a geopolitics of memory in the post-cold war era - María del Pilar Álvarez (Portes: Revista mexicana de estudios sobre la Cuenca del Pacífico, 2016)
Political relations between South Korea and Japan are strongly determined by the Japanese aggressive past in the peninsula. Since the fifteenth century until the late nineteenth century, these countries maintained relations based on equality and mutual befits. This peaceful interaction was broken by the Meiji Revolution (1868), or more specifically, the Treaty of Kanghwa (1876). The territorial ambitions of imperialist Japan and the subsequent incorporation of Korea as a colony in 1910 shaped later political ties. Despite the traumatic oppression suffered for thirty-five years, the need of economically rebuild the country justified to censor historical issues form the 1965 Treaty. However, the past has not been forgotten. Since the 80s, in the regional sphere several historical memory disputes have emerged. This article analyzes the political relations between South Korea and Japan from a historical rereading Samuel Kim (2014)'s systemic theory of East Asia and suggests the need to incorporate a new scenario (or system) called geopolitics of memory in order to understand the current complex situation.